Greater bioavailability of xanthophylls compared to carotenes from orange juice (high-pressure processed, pulsed electric field treated, low-temperature pasteurised, and freshly squeezed) in a crossover study in healthy individuals. (1st March 2022) - Olmedilla-Alonso, Begoña; Granado-Lorencio, Fernando; de Ancos, Begoña; Sánchez-Moreno, Concepción; Martín-Belloso, Olga; Blanco, Inmaculada; Herrero-Barbudo, Carmen; Elez-Martínez, Pedro; Plaza, Lucía; Cano, M. Pilar
Highlights: Serum xanthophylls but not carotenes increased with processed orange juice intake. Xanthophylls α- and β-cryptoxanthin showed the highest responses in the serum. Serum responses to FS and HPP-treated orange juice intake were similar. Higher carotenoids in serum were observed after FS vs. LP orange juice intake. Higher serum responses were observed after FS vs. PEF-treated orange juice intake. Abstract: This study examined the effect of the intake of orange juice provided freshly squeezed (FS) or processed using low-temperature pasteurisation (LP), high-pressure processing (HPP), or pulsed electric field (PEF) treatment on the serum carotenoid concentrations of 12 healthy individuals, aged 20–32 years, enrolled in a crossover study. Participants were instructed to consume 500 ml of orange juice/day for 14 days. Carotenoid concentrations in the orange juice as well as serum samples retrieved on days 7 and 14 were analysed via HPLC. A significant increase in serum xanthophyll concentrations, but not serum carotenes, was observed, with the highest increase in α- and β-cryptoxanthin. The processing technologies applied appeared to affect serum carotenoid concentrations, with concentrations being similar in the HPP and FS orange juice types. As high variability in serum carotenoid concentrations was observed, the effect of different technologies on serum carotenoid concentration warrants further studies with larger sample sizes.